Public health measures to reduce smoking prevalence in the UK: how many lives could be saved?. Issue 4 (26th July 2005) - Lewis, S; Arnott, D; Godfrey, C; Britton, J
Abstract : Objective: To estimate the number of deaths that could be prevented in the UK by implementing population strategies to reduce smoking prevalence. Design: A prospective analysis of future mortality using recent national smoking prevalence data and relative risks of mortality in current smokers, ex-smokers, and never-smokers. Population: Smokers in the UK. Interventions: Population measures of proven effectiveness assumed to reduce smoking prevalence by 1 percentage point per year for 10 years, or alternatively by 13% over 19 years (1 percentage point per annum for seven years, 0.5 percentage point per annum for 12 years) as considered to be achievable in a recent report to the UK Chancellor of the Exchequer. Main outcome measure: Estimated deaths from smoking prevented in the 35–75 year age group. Results: Reducing the prevalence of smoking by 1 percentage point each year for 10 years would prevent 69 049 deaths at ages between 35 and 74 years during that period. The model of reduction by 13% over 19 years would prevent 54 308 and 194 493 deaths in 10 and 19 years, respectively. Continued prevalence reductions at the current rate of 0.4 percentage points each year will prevent 23 192 deaths over 10 years. Conclusions: Full implementation of simple population measures to encourage smoking cessation could prevent substantial numbers of deaths in the UK.